2022
DOI: 10.3390/pharmacy10060146
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the University Pharmacy Education Programs in Germany and Vietnam

Abstract: During the global COVID pandemic, the importance of professionals in the health care sector has been put in a new light, including pharmacists. In this context, the focus is also on how pharmacists are trained in different countries. Through an exchange of pharmacy teaching staff from a German to a Vietnamese university, the pharmacy education programs in both countries were compared. Aspects such as access to studies, structure of studies, and further training opportunities were considered. Differences and si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Nonetheless, pharmacy remains a popular field of study. In Vietnam, the total number of pharmacy students enrolled in public universities in 2020 was 12,466 (Baecker et al, 2022). Despite this, the pharmacy industry in Vietnam still experiences a shortage of personnel.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nonetheless, pharmacy remains a popular field of study. In Vietnam, the total number of pharmacy students enrolled in public universities in 2020 was 12,466 (Baecker et al, 2022). Despite this, the pharmacy industry in Vietnam still experiences a shortage of personnel.…”
Section: Introductionmentioning
confidence: 99%
“…The Ministry of Health has set a goal for clinical pharmacists to account for 30% of all pharmacists, but the actual percentage was reported to be only 3.78% in 2019 (Prime Minister of Vietnam, 2021). Despite the high number of pharmacy graduates each year, there is still a shortage of pharmacists in hospitals and healthcare facilities due to many pharmacists preferring to work in other pharmacy-related fields (Baecker et al, 2022). The Ministry of Health reported that Vietnam became an aging population country in 2011, and it is estimated that the proportion of elderly people living in Vietnam will increase from the current 11% to 18% by 2030 and further to 26% by 2050 (Tien Phong Online, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conventionally, pharmacy students have been provided a series of lectures on medication use to obtain sufficient pharmaceutical knowledge [ 2 ]. However, whether skills for pharmacy practice are well trained is uncertain due to limited training hours in the curriculum across universities in Viet Nam [ 3 , 4 ]. In addition, the internship at a pharmacy only takes place in the final year of the 5-year pharmacy programme and lasts for one week; accordingly, students could hardly conceptualize the pharmaceutical activities and operation procedures at community pharmacies within this short duration [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, whether skills for pharmacy practice are well trained is uncertain due to limited training hours in the curriculum across universities in Viet Nam [ 3 , 4 ]. In addition, the internship at a pharmacy only takes place in the final year of the 5-year pharmacy programme and lasts for one week; accordingly, students could hardly conceptualize the pharmaceutical activities and operation procedures at community pharmacies within this short duration [ 2 , 3 ]. Therefore, a self-learning tool that provides the visualization of pharmaceutical activities in a community pharmacy is necessary, especially when human resources are limited.…”
Section: Introductionmentioning
confidence: 99%